Sex Differences in Outcomes After Tenecteplase for Minor Stroke: A Subanalysis of the TEMPO‐2 Trial - Amy Y. X. Yu; Shabnam Vatanpour; Aravind Ganesh; Thalia S. Field; Philip A. Barber; Philip M. C. Choi; Brian Buck; Timothy Kleinig; Carlos A. Molina; Bruce C. V. Campbell; Ramana Appireddy; Keith W. Muir; et al. (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background In this subanalysis of the TEMPO‐2 (Tenecteplase Versus Standard of Care for Minor Ischaemic Stroke With Proven Occlusion) trial, a randomized clinical trial comparing tenecteplase and nonthrombolytic control in patients with minor stroke and symptomatic intracranial occlusion, we investigated sex differences in the efficacy and safety of tenecteplase. Methods We compared outcomes after tenecteplase versus control, stratified by sex. We also compared outcomes in female versus male patients treated with tenecteplase. The primary outcome was a “responder” outcome, defined as return to baseline modified Rankin Scale score at 90 days. Secondary outcomes included the Lawton Instrumental Activities of Daily Living Scale, the EuroQol‐5 Dimension, vessel recanalization, and adverse events. We used generalized linear modeling with a Poisson distribution adjusted for baseline differences to calculate adjusted risk ratios (aRR) and 95% CIs. Results There were 884 patients in the intention‐to‐treat analysis (48.9% tenecteplase, 41.5% female). Among female participants, the tenecteplase group was less likely to be a responder compared with control (63.8% tenecteplase, 73.9% control, aRR, 0.87 [95% CI, 0.76–1.00]). Among male participants, the responder outcome was similar between groups (77.5% tenecteplase, 75.4% control, 1.03 [95% CI, 0.94–1.13]). Female participants randomized to tenecteplase were less likely to be responders than male counterparts (63.8% female, 77.5% male, 0.85 [95% CI, 0.75–0.96]). Early recanalization was more frequent after tenecteplase than control in both sexes. Conclusions Tenecteplase was not associated with better clinical outcomes over nonthrombolytic control in female or male patients with minor ischemic stroke, despite more frequent recanalization. Fewer women treated with tenecteplase returned to baseline function compared with men.